The taxonomic composition of the donor intestinal microbiota is a major factor influencing the efficacy of faecal microbiota transplantation in therapy refractory ulcerative colitis. Issue 1 (20th October 2017) - Kump, P.; Wurm, P.; Gröchenig, H. P.; Wenzl, H.; Petritsch, W.; Halwachs, B.; Wagner, M.; Stadlbauer, V.; Eherer, A.; Hoffmann, K. M.; Deutschmann, A.; Reicht, G.; et al.
Summary: Background: Faecal microbiota transplantation is an experimental approach for the treatment of patients with ulcerative colitis. Although there is growing evidence that faecal microbiota transplantation is effective in this disease, factors affecting its response are unknown. Aims: To establish a faecal microbiota transplantation treatment protocol in ulcerative colitis patients, and to investigate which patient or donor factors are responsible for the treatment success. Methods: This is an open controlled trial of repeated faecal microbiota transplantation after antibiotic pre‐treatment (FMT‐group, n = 17) vs antibiotic pre‐treatment only (AB‐group, n = 10) in 27 therapy refractory ulcerative colitis patients over 90 days. Faecal samples of donors and patients were analysed by 16SrRNA gene‐based microbiota analysis. Results: In the FMT‐group, 10/17 (59%) of patients showed a response and 4/17 (24%) a remission to faecal microbiota transplantation. Response to faecal microbiota transplantation was mainly influenced by the taxonomic composition of the donor's microbiota. Stool of donors with a high bacterial richness (observed species remission 946 ± 93 vs no response 797 ± 181 at 15367 rps) and a high relative abundance of Akkermansia muciniphila (3.3 ± 3.1% vs 0.1 ± 0.2%), unclassified Ruminococcaceae (13.8 ± 5.0% vs 7.5 ± 3.7%), and Ruminococcus spp. (4.9 ± 3.5% vs 1.0 ± 0.7%) were more likely to induce remission. In contrast antibiotic treatment alone (AB‐group) was poorly tolerated, probably because of a sustained decrease of intestinal microbial richness. Conclusions: The taxonomic composition of the donor's intestinal microbiota is a major factor influencing the efficacy of faecal microbiota transplantation in ulcerative colitis patients. The design of specific microbial preparation might lead to new treatments for ulcerative colitis.